In land we trust - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
In land we trust - environment, private property and constitutional change by Calestous Juma and J B Ojwang 1996 462pp ISBN 1 85649 418 7 Pbk